Ischemic necrosis of the femoral head: An experimental rabbit model. Issue 4 (21st January 2015) - Tudisco, Cosimo; Botti, Flavia; Bisicchia, Salvatore; Ippolito, Ernesto
ABSTRACT: To describe the morphology of the proximal femoral epiphysis in a rabbit model from the ischemic insult to the end of the revascularization process. Ischemia of the femoral head was induced in 32 rabbits at the 8th day of life, by sectioning the joint capsule and the ligamentum teres and dislocating the femoral head. Rabbits were sacrificed at 4, 8, 12, 18, 21, 26, 34, and 48 days after surgery and femoral heads were observed histologically. During the first days following the ischemic injury, large areas underwent necrotic changes. Both epiphyseal and physeal cartilage were thicker than normal and less trabecular bone formation was evident. Bone marrow was also diffusely necrotic within the secondary center of ossification. After day 12th, reparative process started with formation of extensive areas of fibrocartilage and several secondary centers of ossifications. At that stage femoral head deformity was already evident. In the following days the secondary centers of ossification cohalesced and epiphyseal and physeal cartilage resumed a normal appearance, but the femur showed a permanent deformity. In newborn rabbits, the ischemic injury to the femoral head blocked the ossification of the epiphyseal and physeal cartilage associated to necrotic bone marrow within the secondary center of ossification of the femoral head as well as to extensive areas of necrosis of epiphyseal and physeal cartilage. Extensive areas of fibrocartilage and small newly formed ossification centers within the femoral epiphysis were the results of the revascularization process, and femoral head deformity became stable afterward. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:535–541, 2015.